Qualitative research in rehabilitation science: opportunities, challenges, and future directions. Issue 6 (13th March 2018) - VanderKaay, Sandra; Moll, Sandra E.; Gewurtz, Rebecca E.; Jindal, Pranay; Loyola-Sanchez, Adalberto; Packham, Tara L.; Lim, Chun Y.
Abstract: Purpose: Qualitative research has had a significant impact within rehabilitation science over time. During the past 20 years the number of qualitative studies published per year in Disability and Rehabilitation has markedly increased (from 1 to 54). In addition, during this period there have been significant changes in how qualitative research is conceptualized, conducted, and utilized to advance the field of rehabilitation. The purpose of this article is to reflect upon the progress of qualitative research within rehabilitation to date, to explicate current opportunities and challenges, and to suggest future directions to continue to strengthen the contribution of qualitative research in this field. Methods: Relevant literature searches were conducted in electronic data bases and reference lists. Pertinent literature was examined to identify current opportunities and challenges for qualitative research use in rehabilitation and to identify future directions. Results: Six key areas of opportunity and challenge were identified: (a) paradigm shifts, (b) advancements in methodology, (c) emerging technology, (d) advances in quality evaluation, (e) increasing popularity of mixed methods approaches, and (f) evolving approaches to knowledge translation. Two important future directions for rehabilitation are posited: (1) advanced training in qualitative methods and (2) engaging qualitative communities of research. Conclusion: Qualitative research is well established in rehabilitation and has an important place in the continued growth of this field. Ongoing development of qualitative researchers and methods are essential. Implications for Rehabilitation: Qualitative research has the potential to improve rehabilitation practice by addressing some of the most pervasive concerns in the field such as practitioner–client interaction, the subjective and lived experience of disability, and clinical reasoning and decision making. This will serve to better inform those providing rehabilitation services thereby benefiting patients that are utilizing these services. Changes over time in how qualitative research is conceptualized, conducted, and utilized to advance rehabilitation science have resulted in a number of unique opportunities and challenges in using qualitative research that must be considered within this field. Advances in methodology and increased expectations for evaluation must be considered to ensure quality and credibility of qualitative rehabilitation research within rehabilitation. Improved quality and credibility may increase likelihood of research dissemination and use by clinicians intervening within the rehabilitation process in order to improve clinical practice. In order to maximize opportunities and mitigate challenges there are two principal future directions for rehabilitation scientists to consider: (1) advancing training in qualitative methods to adequately prepare future rehabilitation scientists and (2) engaging qualitative communities of research.